Character education in the Islamic law - Ahmad Alfurqan Suyono (IAIN Salatiga, 2021)
Education must have a good and robust foundation, because with this foundation, the direction of the implementation of education is not merely a momentary shock or turmoil. The foundation of knowledge is an essential in the process of advancingeducation. The aim of this study is to find out how is the importance of charactereducation from the Islamic point of view. The data were gained through library research or document research. The result shows the importance of character education from Islamic law insight. The basis of education is a fundamental problem because the primary school will determine the style and content of learning. In the meantime, its relation to Islamic teaching, the basis or foundation of Islamic education, is the foundation that forms the basis or principle to stand tall. Therefore, the basis of Islamic culture must be considered comprehensively in revealing through the next educational steps. Al-Qur'an and Hadith are sources of Islamic law and complete knowledge, covering the whole of human life, both the world and the hereafter. Both become an apparent clue for humans and the pace of their lives at all times.